LOCAL ECONOMIC EMPOWERMENT: STRATEGIES AND IMPLEMENTATION - Loso Judijanto; Amândio de Araújo Sarmento; Mohd Syahrin; Mohamad Khairi Bin Haji Othman; Al-Amin (Adisam Publisher, 2024)
Local economic empowerment plays a crucial role in sustainable economic growth, focusing on improved access to finance, education and employment training, appropriate infrastructure, and the implementation of proactive government policies. The strategy emphasizes the importance of integration and collaboration among various stakeholders, including governments, communities, and the private sector, to create an ecosystem that supports innovation, entrepreneurship, and local business development. The research methods carried out on this study are literature. Research results show that the success of local economic empowerment depends heavily on how much the local community is involved in program planning and execution. Access to broader financial resources, targeted and relevant education and training, as well as infrastructure development to meet local specific needs, have proven to be key drivers of economic growth. Government policies that support, through incentives and facilities, are also decisive in supporting this economic activity.